Analisis Strategi Diferensiasi dan Trust Dalam Pembelian Jasa Pendidikan Islam (Studi Kasus terhadap SMP IT Al Fityan School Kubu Raya) - B11107090, M. Arsyad (Jurnal Manajemen Update, 2014)
Education is very important for human life. Many educational institutions provide additional features to meet their user need and want. To survive, each school has to formulate and implement well designed competitive strategies. Further, school must produce and develop a unique strategy including product differentiation, service differentiation, image differentiation and trust. This strategy provides company`s competitive advantage which ultimately affects consumer`s buying decision. The objective of this study is to analyze differentiation strategies (product, service and brand image) and trust that influence buying decision in SMP IT Al Fityan Kubu Raya. By using systematic sampling technique, 100 respondents are chosen. They are the parents of student in SMP IT Al Fityan Kubu Raya. Employing Linier Regression Technique, the study found that five factors, product differentiation, service differentiation, brand image differentiation, and trust has a significant and positive effect influence on consumer`s buying decision. This result shows that the study support theories and previous findings from Lestari (2005), Syukri (2006), Masruri (2006), and Rofiq (2007). Keywords: product differentiation, service differentiation, brand image differentiation, trust, and buying decision